The Activity of Agritourism Farms in Podlaskie Voivodeship in the Opinions of Their Owners - Sokół Janusz Leszek (Studia Ekonomiczne i Regionalne, 2017)
Subject and purpose of work: The purpose of this study was to analyse and evaluate the operation of argritourism farms in Podlaskie Voivodeship (voivodeship is an equivalent of province in Polish administration), conducted with regard to their structure and market functioning, and the possibility of using the advisory and financial support existing in the region. Materials and methods: The research had a survey form and was conducted in the second half of 2014 on a sample of 120 agritourism farms, which constitutes more than 13% of all entities in Podlaskie Voivodeship. Results: Most of the agritourism farms in the Podlaskie Voivodeship are ones that do not exceed the area of 5 hectares. They are focused on hosting individual guests and families with little children. The majority of farm owners do not have adequate experience in providing agritourism services. The activity of agritourism farms is based primarily on the proprietary capital. Conclusions: Better education and more complete information about the possibilities and ways of obtaining financial support seem to be the key to a more dynamic and efficient development of agritourism in the rural areas of Podlaskie Voivodeship.